Morphology and phylogeny of Pseudocercospora morigena sp. nov. on Morus alba from Vindhya Range, India - Singh, Archana; Singh, Paras Nath; Kharwar, Ravindra Nath; Dubey, Nawal Kishore (Phytotaxa, 2023)
Pseudocercospora morigena (Mycosphaerellaceae, Mycosphaerellales) was discovered causing severe foliar leaf spot disease of Morus alba. Identity of the new species is based on morphology, culture characteristics and molecular analyses from three gene regions, internal transcribed spacer regions with intervening 5.8S nrRNA gene (ITS), translation elongation factor 1-alpha gene (TEF1-α) and actin gene (ACT). Morphologically, the present species differs from the allied species reported on the same host genus by the presence of superficial mycelium giving rise to solitary conidiophore, stromata filling stomatal opening and geniculate conidiophores.